Fun With Pascal's Triangle

  • May 2020
  • PDF

This document was uploaded by user and they confirmed that they have the permission to share it. If you are author or own the copyright of this book, please report to us by using this DMCA report form. Report DMCA


Overview

Download & View Fun With Pascal's Triangle as PDF for free.

More details

  • Words: 2,046
  • Pages: 5
FUN WITH PASCAL'S TRIANGLE Paul Jackson, 2009 Consider Pascal's Triangle...

1 1 1 1 1 1

3

5

7

6

15

.

1 4

10 20

35 .

1 3

10

21

.

2

4

6

1

5 15

35 .

1 1 6

1

21 .

7 .

1 .

.

.

Let the diagonal elements be called tn so the triangle numbers would be t3 for example. Of course n−1r these each form infinite sequences. Then in general tn = . We shall show that r ∞  n−1  ∑ t1 =  n−2 , for n≥3 . r=0 n







We also know that the sums of the reciprocals of t1 and t2 are both divergent. Using elementary methods we find that for n = 3, 4 , 5 the sums are 2/1, 3/2, 4/3 respectively, so we seek to generalize on these first results. To find these sums we invert the general formula for tn and after factoring out the common numerator we get a general term that is the reciprocal of a product of factors in arithmetic progression.

1

Special case So as an example; for n = 5 we have a general term, 4r 1 4! = 1/ = , for r = 0 , 1 , 2 ... r t5  r1  r2  r3  r 4  Now just to make the structure a little clearer we put r +1 = r , for r = 1 , 2 , 3 ,... That is we have 1 redefined r to begin at r = 1 instead of zero. Then we need to express in  r  r 1  r 2  r3  partial fractions. So we have a general term:



 





1 1 3 3 1 −  − . Then when we sum to infinity we find all except the first 3! r  r1   r2   r3  few terms disappear, in fact we get the following pattern for the terms inside the brackets: 1 3 3 1 −  − 1 2 3 4 +

1 3 3 1 −  − 2 3 4 5

+

1 3 3 1 −  − 3 4 5 6

+

1 3 3 −  - .. 4 5 6

1 . . . etc. We see that the terms diagonally starting from the top 5 right corner must equal zero, as they all have the same denominator and the numerators are just the value of 1−x 3 when x = 1. So we see that we are just left with the first upper triangle of terms. 1 Now curiously when we sum these we find the value is just , hence we see that the sum we 3 4 require is just . 3 Now for the general case we find the same pattern occurring that is the first upper triangle of terms 1 has value  n−2  , we shall next prove this is the case. +

2

Toward the general case In general using the above example we would need to express partial fractions, that is we need: 1 =  r  r1 r2  .........  rk 

1 in  r  r 1 r 2  .........  r k 

A0 A1 A2 Ak   + .........+ . [1] r  r1   r 2   r k 

We have k terms and k Ai coefficients to evaluate. Say we wished to evaluate an arbitrary coefficient Ai , then we simply multiply [1] throughout by (r+ i) . In the left hand side of [1] this term will cancel out, and on the right hand side each term except the one with coefficient Ai will be multiplied by (r+ i). Now when we put r = -i into both sides of our expression, we are left with the value of Ai alone, the other terms on the right hand side being each zero. So for each i = 0, 1, 2 , 3, .......k we can evaluate [1] and nowhere on the left hand side will we get a zero in the denominator. Also in general the sign of Ai depends on the sign of the denominator

 r  r1  r2  .........  ri−1 ri1  ri2 ............  rk  in the left hand side of [1]. We see that the product of terms after r + i- 1 is positive, and as there are i terms before and including this term which will all be negative, when we substitute for r = i, we see the sign of Ai is just (-1)i .

 .

i i 1 k −1   So we find Ai = = = −1 k ! i  i  i−1  i−2  ......... 3 . 2 .1 .1 . 2 . 3........  k −i  i! k −i !

−1 

i

ki  , then A =

Bi . So we see that in our general expression the k! numerators in the array of fractions with denominators in arithmetic progression starting 1, 2 3... as in the case for n = 5 above, will be binomial coefficients, of the appropriate row of Pascal's Triangle, and hence each diagonal of n terms will sum to zero as in the case illustrated above, and thus the sum of the series will depend on the sum of the upper left triangle of terms, which we need 1 to show is always equal to .  n−2 Hence if we let Bi =

i

−1i

Now when we form upper left triangle of terms as we did above, for the next case, n = 6, that is k =4, and when we sum the diagonals of non disappearing terms we find for we have; 1 3 3 1 −  − , that is the first three non disappearing terms for the triangle for k = 3, plus the 1 2 3 4 extra term. The pattern is the same for the next few values of k. It seems possible that we can generate the next sum of the upper right triangle from the previous one. This should not be too surprising as we are dealing with binomial coefficients, in the form of Pascal's triangle, that seems to be mapped in slightly strange ways. It would appear that as we manipulate this structure the same coefficients keep popping up. 3

Now consider the diagonal elements in the triangle for k =4. The first diagonal sum d1 = 1, 1 4 1−4 −3 − = second diagonal sum d2 = = , 2 2 2 2 the third d3 = 1−46 = −36 = 3 , and lastly 3 3 3 1−46−4 −1 the fourth d4 = = . 4 4 But of course 4 = 1+3, so we are undoing the formation of the next line of coefficients in Pascal's triangle. In fact we can reverse the procedure we have just accomplished to generate the upper right triangle of terms for k = 4 from k = 3. So we have;

1 3 3 −  and we expand these to give: 1 2 3

1 , the next diagonal has two terms, so from Pascal's triangle 1+3 = 4, so – 3 = 1 – 4 , so this is 1 the next coefficient to be expanded −3 1−4 1 4 − , the next term we need is the sum of 3 + 3 = 6, so 3 = -3 + 6, using the = = 2 2 2 2 last starting number. 3 −36 1−46 = = ,as -3 = 1- 4 from above, we then plug 3 into the next diagonal 3 3 3 expansion as -1 = 3 – 4 . For the last diagonal we know it has k terms, and we know that the sum of the terms 1 – 4 + 6 – 4 +1 is zero, so the sum of 1 – 4 + 6 – 4 = -1, therefore the sum of the upper left diagonal for k = 4 is 1 3 3 −1 1 −  and just the sum of which is as required. 1 2 3 4 4 So in this particular case we will be able to find the the value of the upper triangle for k = 4 if we knew the value of the first row of the upper triangle for k = 3. This is because we can always easily deduce the value of the last diagonal for the upper triangle for k = 4, using binomial theorem in the expansion of (1- x )4 when x = 1. To generalize this we need some notation. Let the the first row of the upper triangle for k be denoted by Rk , and the upper triangle, and last diagonal for k + 1 be denoted by Uk+1 and dk+1 respectively. Then the value of dk+1 is just the value ∓1 of (1 – x )k+1 when x = 1, (which is zero of course), without the last term this being . k 1

4

Hence Uk+1 = Rk - dk+1 . So we would solve this problem if we knew in general the value of Rk . This is easy to find for small values of k . Which we tabulate below. k

1

2

3

4

Rk

1

0

1/2

0

5 1/3

6

7

8

0

1/4

0

This again seems to imply interesting symmetry properties of the expressions for Rk and the binomial coefficients, but we leave that aside to solve the current problem. Now recall the example for k = 3 at the start of the discussion above we had the expression:





1 1 1 3 3 1 −  − = expressed on the right hand side 3! r  r1   r 2   r 3   r  r1  r2  r3  in partial fractions, now when we let r = 1, and rearrange we get 3! 1 3 3 1 1 −1 = but this is just R3 with the extra term! So we see that R3 = −  − −  4! 1 2 3 4 4 4 1 = as we expected. It is not hard to extend this example to the general case, from which we find 2 2 that Rk has value zero if k is even, and value if k is odd, remembering from above that k 1 B Ai = −1i i so the Bi are the binomial coefficients, or numerators in Rk . k!





Therefore we see that the result Uk+1 =

1 = k

1 follows, and so does what we set out to n−2

initially show, that is;



 n−1  1 = , for n3 . tn  n−2  r=0 Finally we note in passing the similarity of this expression to ∞ ∞ 1 r r −1r n−1r x r = n , which if valid in the context of infinite ∑ −1 t n x = ∑ r  1x  r=0 r=0 series, would give, when we put x = 1, the value of the reciprocal of the nth row in Pascal's triangle. It is almost as if we have a mapping of the diagonals of Pascal's Triangle to the rows. 1  n−1  We seem to have a function f :  , for n3 n∈ℕ .  n−2  2n The above expression is a generating function, so it would seem we can put : ∞











n









xr = ∑ −1r n−1r ∑ −1 x r r=0 r=0 power of the standard Geometric Series. r

r

=

  1 1 x

n

as the last expression is just the nth

We also note that there other manipulations of Pascal's Triangle that lead to the Fibonacci sequence and Lucas sequences in general, and thence to Pell's equation and second order recurrence relations and beyond. 5

Related Documents